Modulating self-biased near-UV photodetection of Gd-doped bismuth ferrite ceramics by introducing zinc oxide as electron transport layer. Issue 2 (15th January 2023) - Mana-ay, Haidee; Zhang, Shao-Yu; Chen, Cheng-Sao; Tu, Chi-Shun; Chen, Pin-Yi
Abstract: ZnO semiconductor offers many advantages as an electron transport layer (ETL) in photovoltaic-based devices, including high charge carrier mobility and hole-blocking ability. In this work, ZnO thin film is introduced as an ETL between (Bi0.93 Gd0.07 )FeO3 (BFO7Gd) ferroelectric and ITO thin film to form ITO/ZnO/BFO7Gd/Au heterostructure. The device with the ETL exhibited a superior photoresponsivity than the one without ETL, reaching ∼32% enhancement. Furthermore, a subsequent E -field poling on the ITO/ZnO/BFO7Gd/Au heterostructure resulted in an additional ∼25% increase in photoresponsivity. The enhancement is mainly attributed to two factors: (1) high electron mobility and lower recombination rate resulting from the introduction of ZnO ETL, and (2) efficient charge separation facilitated by the polarization-driven internal E field that superimposes with the interfacial built-in E fields. The introduction of ZnO ETL and the utilization of the ferroelectric polarization prove to be an alternative route to further modulate the photosensing performance of BiFeO3 -based near-UV photodetectors.